Dynamics of gyrostat satellite subject to gravitational torque: Investigation of equilibria - Sarychev, Vasili (2022)
Dynamics of gyrostat satellite moving along a circular orbit in the central Newtonian gravitational field is investigated. A symbolic-numerical method for determining all equilibrium orientations of gyrostat satellite in the orbital coordinate system with given gyrostatic torque and given principal central moments of inertia is proposed. Conditions of equilibriums existence are obtained depending on four dimensionless parameters of the system. All bifurcational values of parameters at which there is a change of numbers of equilibrium orientations are determined. Evolution of domains in the space of parameters which correspond to various numbers of equilibria are carried out in detail. Relationship with axisymmetrical cases of satellite gyrostat is considered. It is shown that the number of equilibria of the gyrostat satellite in general case not be less than 8 and not more than 24.